Determining the track condition using soil properties - part 1. (October 2019) - Schuk, V; Rapp, S; Martin, U; Wang, B
Abstract: The track condition in conventional ballast construction is decisively determined by the condition of the sub-ballast and the subgrade. An indicator for the assessment of the track condition is the track modulus, which can be calculated by measuring the rail deflection under load or according to the soil properties. The track modulus describes the ratio between vertical loading and elastic deflection of the sleeper support. This is the first of two papers concerning a theoretical approach to estimate the track modulus of the soil by soil properties. The approach's advantage is to be completely independent from the superstructure condition. Therefore the components of the superstructure along the track axe must not know for calculating the track modulus. Borings with direct ground exploration results and ground penetrating radar measurements are used to determine the soil condition at the track level. After the allocation of the soil properties to each layer, the cone model is used to calculate this average value of the soil properties. Subsequently, the track modulus of the soil is determined by using the average value of the soil properties. Based on the value of the track modulus of the soil, the track condition can then be determined.